Substitution of Concentrate with Mulberry Leaves in Ongole Grade Cattle Fed Rice Straw Based Diet - S Syahrir; K G Wiryawan; A Parakkasi; M Winugroho; A Natsir (Media Peternakan, 2012)
An experiment was conducted to assess the substitution of concentrate with mulberry (Morus spp.) leaves combined with rice straw offered to beef cattle. The study used 12 male Ongole grade cattle weighing 217+10.53 kg. Rations consisted of rice straw, mulberry leaves and concentrate. Research was carried out according to completely randomized design with 3 treatments and 4 replications for each treatment. The treatments were: P1= 50% rice straw + 50% concentrate; P2= 50% rice straw + 25% concentrate + 25% mulberry; P3= 50% rice straw + 50% mulberry. The results of the study indicated that rumen fermentation in cattlle fed on P2 ration was more effective than those receiving P1 and P3 rations. The fermentation was characterized by a higher production of total VFA and allantoin excretion in the urine. The presence of 1-deoxynojirimycin  (DNJ) compound of mulberry leaves in the rumen system in treatment P2 and P3 improved digestibility of fiber fractions of rice straw-based rations. Mulberry leaves in rations also accounted for isoacids in the rumen system, which supported the development of cellulolytic bacteria. In conclusion, mulberry leaves containing concentrate had a potency to substitute concentrate when used together with  fiber source feed such as rice straw.